The Role of Personality Traits in Young Adult Fruit and Vegetable Consumption - Conner, Tamlin S.; Thompson, Laura M.; Knight, Rachel L.; Flett, Jayde A. M.; Richardson, Aimee C.; Brookie, Kate L. (Frontiers in Psychology, 2017)
This project investigated how individual differences in the big-five personality traits (neuroticism, extraversion, openness to experience, conscientiousness, and agreeableness) predicted plant-food consumption in young adults. A total of 1,073 participants from two samples of young adults aged 17 to 25 reported their daily servings of fruits, vegetables, and two unhealthy foods for comparison purposes using an Internet daily diary for 21 or 13 days (micro-longitudinal, correlational design). Participants also completed the Neuroticism, Extraversion, Openness Five Factor Inventory (NEO-FFI) measure of personality and demographic covariates including gender, age, ethnicity, and body mass index (BMI). Analyses used hierarchical regression to predict average daily fruit and vegetable consumption as separate dependent variables from the demographic covariates (step 1) and the five personality traits (step 2). Results showed that young adults higher in openness and extraversion, and to some extent conscientiousness, ate more fruits and vegetables than their less open, less extraverted, and less conscientious peers. Neuroticism and agreeableness were unrelated to fruit and vegetable consumption. These associations were unique to eating fruit and vegetables and mostly did not extend to unhealthy foods tested. Young adult women also ate more fruit and vegetables than young adult men. Results suggest that traits associated with greater intellect, curiosity, and social engagement (openness and extraversion), and to a lesser extent, discipline (conscientiousness) are associated with greater plant-food consumption in this population. Findings reinforce the importance of personality in establishing healthy dietary habits in young adulthood that could translate into better health outcomes later in life.